Ways of Semantic Derivation and Types of Relations between Meanings in Adjective Semantic Structure - M. V. Sandakova (Научный диалог, 2019)
The polysemy of an adjective as a semantic and grammatical phenomenon is studied. The semantic structure of a polysemantic adjective and the character of motivational relations between its lexico-semantic variants are analyzed. The connection between the method of semantic derivation, the semantic type of lexical meaning generated by it and the lexeme belonging to a particular lexico-grammatical category is investigated. The representation of adjectival polysemy in a dictionary entry is described. The novelty of the study is seen in the fact that the author sets the task of inventory and systematization of ways of semantic derivation of an adjective, among which metaphorical transfer, metonymic transfer, specialization of relations are distinguished. It is proved that in the semantic structure of polysemantic adjective two types of motivational relations between meanings are possible: direct motivation and parallel (mediated) motivation. The types of relations between initial and secondary meanings according to their discharge affiliation are revealed: relative - relative; qualitative - qualitative; relative - qualitative; qualitative - relative. Adjectival semantic neologisms are described. It is noted that most of them are not fixed in explanatory dictionaries, only in the dictionaries of the 21st century it is possible to identify some adjectives formed by specialization, which is an active way of secondary qualitativeness derivation.